2007
DOI: 10.4137/117739010700200001
|View full text |Cite
|
Sign up to set email alerts
|

Role of99mTc-(V)DMSA in Detecting Tumor Cell Proliferation

Abstract: Pentavalent technetium-99m dimercaptosuccinic acid ( 99m Tc-(V)DMSA) is a tumor-seeking agent which was introduced to evaluate, image, and manage many types of cancers. In this review, the beginning of, and the most recent applications of using this agent was appraised. The relation with tumor cell detection and proliferation was reported and several mechanisms of uptake of 99m Tc-(V)DMSA in tumor cells are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Other studies showed a relation between the in vivo 99m Tc(V)-DMSA uptake and the proliferation rate measured by the expression of Ki-67 and by the phosphorylated focal adhesion kinase [27]. It was also described an inverse relation between pH and 99m Tc(V)-DMSA uptake, where glucose-mediated acidosis stimulated 99m Tc(V)-DMSA uptake [28].…”
Section: Case Reportmentioning
confidence: 94%
See 2 more Smart Citations
“…Other studies showed a relation between the in vivo 99m Tc(V)-DMSA uptake and the proliferation rate measured by the expression of Ki-67 and by the phosphorylated focal adhesion kinase [27]. It was also described an inverse relation between pH and 99m Tc(V)-DMSA uptake, where glucose-mediated acidosis stimulated 99m Tc(V)-DMSA uptake [28].…”
Section: Case Reportmentioning
confidence: 94%
“…The 99m Tc(V)-DMSA is a nonspecific tumor-seeking agent, initially used for the evaluation of medullary thyroid carcinoma. Its usefulness has also been reported in the evaluation of many other types of cancer, such as head and neck, soft tissue, and breast [27,28]. Its mechanism of uptake is thought to be due to the structural similarity between 99m Tc-(V)DMSA core (phosphate-like ion TcO 4 ) anion [28].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…99m Tc(V)-DMSA is a well-known tumor-seeking radiotracer with affinity for neuroendocrine and soft tissue tumors, such as medullary thyroid carcinoma and lung, breast, brain, and metastatic bone lesions [Ohta et al, 1984, Babbar et al, 1991, Kashyap et al, 1992, Hirano et al, 1995, Atasever et al, 1997, Lam et al, 1997, Kiratli et al, 1998, Papantoniou et al, 2002, 2010, Denoyer et al, 2004, Tsiouris et al, 2007, Al-Saeedi, 2007. These tumor-seeking properties have lead to the use of 99m Tc(V)-DMSA in scintimammographic studies.…”
Section: M Tc(v)-dmsa Scintimammographymentioning
confidence: 99%
“…The biokinetic characteristics of 99m Tc(V)-DMSA support our suggestion that the observed reduction in its uptake could be attributable to ibuprofen-induced COX inhibition and may indicate a "switch off" mechanism on activated FAK, rather than a slowing down of the proliferation rate per se. 99m Tc(V)-DMSA cellular uptake is linked to FAK activation and cell proliferation, which is a precocious stage of malignant transformation [Papantoniou et al 2004, Le Jeune et al 2005, Al-Saeedi, 2007. Compared to invasive lesions, the exact mechanism of 99m Tc-(V)DMSA accumulation in benign proliferating diseases and in some non-proliferating diseases with higher lesion-tobackground tracer uptake ratios is not yet clear [Papantoniou et al 2004[Papantoniou et al , 2006b].…”
Section: M Tc(v)-dmsa Scintimammographymentioning
confidence: 99%